Strategic Processes in Georgian Manufacturing Companies – Business-Level Strategy Perspective - Khoshtaria, Tornike (Management and Administration Journal, 2019)
The purpose of this study is to examine the links between generic strategy types and organizationalperformance. Moreover, this paper will attempt to discover whether or not the emphasis onplanning strategy implementation will enhance a company with superior performance. This paperstudied 104 Georgian based manufacturing companies. A questionnaire was chosen as the surveyinstrument. The respondents selected were CEOs of the manufacturing companies being surveyed.Findings of this study are based on the results of the hypotheses tests which indicate that companieswith clearly defined business strategies are performing better. The group of companies with integratedstrategies had better performance than those concentrating on either of them. This contradicts theidea that it is not effective to use a combination of cost-leadership and differentiation strategy becauseof their exclusivity. There were no strong ties established between the strategic type and the planningof strategic implementation. Moreover, companies placing emphasis on planning strategy implementationhave better performances than those “stuck in the middle”. The results of this study are particularlyuseful for practitioners, as it can provide managers with the information connected with strategyformulation and implementation processes. This study makes a contribution to the existing literatureby exploring strategy processes within Georgian based manufacturing companies, and addressing theinconclusiveness of the results of generic strategies and organizational performance.